A microRNA expression and regulatory element activity atlas of the mouse immune system - Rose, Samuel A.; Wroblewska, Aleksandra; Dhainaut, Maxime; Yoshida, Hideyuki; Shaffer, Jonathan M.; Bektesevic, Anela; Ben-Zvi, Benjamin; Rhoads, Andrew; Kim, Edy Y.; Yu, Bingfei; Lavin, Yonit; Merad, Miriam; et al. (Nature Immunology, 2021)
To better define the control of immune system regulation, we generated an atlas of microRNA (miRNA) expression from 63 mouse immune cell populations and connected these signatures with assay for transposase-accessible chromatin using sequencing (ATAC–seq), chromatin immunoprecipitation followed by sequencing (ChIP–seq) and nascent RNA profiles to establish a map of miRNA promoter and enhancer usage in immune cells. miRNA complexity was relatively low, with >90% of the miRNA compartment of each population comprising <75 miRNAs; however, each cell type had a unique miRNA signature. Integration of miRNA expression with chromatin accessibility revealed putative regulatory elements for differentially expressed miRNAs, including miR-21a, miR-146a and miR-223. The integrated maps suggest that many miRNAs utilize multiple promoters to reach high abundance and identified dominant and divergent miRNA regulatory elements between lineages and during development that may be used by clustered miRNAs, such as miR-99a/let-7c/miR-125b, to achieve distinct expression. These studies, with web-accessible data, help delineate the cis-regulatory elements controlling miRNA signatures of the immune system.
CRIS-Team Scopus Importer:2023-10-02